The Effect of Principal's Leadership, Work Motivation, and School Culture on Teacher Performance at Muhammadiyah Elementry Schools in Gamping Subdistrict - Rini Ratnaningsih; Septian Aji Permana; Agus Joko Purwanto (Universitas PGRI Yogyakarta, 2023)
Teachers have a significant contribution to the learning success in schools. In creating conducive school, having good quality and generating graduates with integrity, good teachers’ performance is needed. Good teachers’ performance is affected by several factors including the principal's leadership, work motivation, and school culture. This study aims at analyzing whether there is a relationship between the principal's leadership, work motivation, and school culture with teachers’ performance. This research was conducted on classroom teachers at Muhammadiyah Elementary Schools in Gamping District with a population of 116. The sample used was the total population of 116. The independent variables in this study were the principal's leadership, work motivation, and school culture, while the dependent variable was teachers’ performance. The measurement of the variables was carried out by using a Likert scale. Data analysis was carried out by using multiple linear regressions with the help of SPSS 22 software. Based on the simple regression test and multiple linear regressions, the test results show that there is a significant relationship between the independent variables, the principal's leadership, work motivation and school culture on the performance of classroom teachers at Muhammadiyah Elementary Schools in Gamping District. The results of the coefficient of determination (R2) test show that teachers’ performance (Y) can be explained by the variables of the principal's leadership (X1), work motivation (X2), and school culture (X3) by 65%, while the remaining 35% is affected by other factors outside of this study. The conclusion of this study is that there is a positive and significant influence between the principal's leadership, work motivation, and school culture on the performance of classroom teachers in Muhammadiyah Elementary Schools in Gamping Subdistrict.